Nerve growth factor and S100B: Molecular marker of neuroregeneration after injection of freeze-Dried platelet rich plasma - Rahmi; Desiana Radithia; Bagus Soebadi; Adiastuti Endah Parmadiati; Saka Winias (Journal of Oral Biology and Craniofacial Research)
Introduction: Chronic orofacial pain is associated with nerve tissues damage. Pharmacological therapy has limited therapeutic results because it is generally only symptomatic treatment. Neuroregeneration is a process which is needed to repair damaged of nerve tissue through healing or regrowth of nerve tissue. The survival of nerve cells need neurotrophic factors including Nerve Growth Factor (NGF) and S100B. High platelet concentrations in Platelet Rich Plasma contain of many trophic factors which play an important role in peripheral nerve regeneration following nerve injury. The aim of the present study is to analyze the increased expression of NGF and S100B following injection of Freeze-Dried Platelet Rich Plasma (FD-PRP) on axonotmesis injury. Methods: Fifty-four male wistar rats aged 3 months randomly divided into 3 groups; negative control group (without nerve injury and without FD-PRP injection), positive control group (nerve injury but without FD-PRP injection) and treatment group (nerve injury and FD-PRP injection). Axonotmesis nerve injury created by clamping the infraorbital nerve for 15 s. Application of FD-PRP by injection technique. Examination of NGF and S100B expression was obtained by immunohistochemistry examination with monoclonal antibodies (anti-NGF and anti-S100B). Samples were taken on the 14th day and 21st day. Results: Treatment group showed significant increase on both NGF and S100B compare to positive control (p = 0,000 and p = 0,000, respectively). Conclusion: FD-PRP injection is effective in inducing neuroregeneration by increasing NGF and S100B expression.